Evolution of the dynamic changes in functional cerebral oxidative metabolism from tissue mitochondria to blood oxygen - Vazquez, Alberto L (Nature Publishing Group, 2012)
The dynamic properties of the cerebral metabolic rate of oxygen consumption (CMR(O2)) during changes in brain activity remain unclear. Therefore, the spatial and temporal evolution of functional increases in CMR(O2) was investigated in the rat somato-sensory cortex during forelimb stimulation under a suppressed blood flow response condition. Temporally, stimulation elicited a fast increase in tissue mitochondria CMR(O2) described by a time constant of ∼1 second measured using flavoprotein autofluorescence imaging. CMR(O2)-driven changes in the tissue oxygen tension measured using an oxygen electrode and blood oxygenation measured using optical imaging of intrinsic signal followed; however, these changes were slow with time constants of ∼5 and ∼10 seconds, respectively. This slow change in CMR(O2)-driven blood oxygenation partly explains the commonly observed post-stimulus blood oxygen level-dependent (BOLD) undershoot. Spatially, the changes in mitochondria CMR(O2) were similar to the changes in blood oxygenation. Finally, the increases in CMR(O2) were well correlated with the evoked multi-unit spiking activity. These findings show that dynamic CMR(O2) calculations made using only blood oxygenation data (e.g., BOLD functional magnetic resonance imaging (fMRI)) do not directly reflect the temporal changes in the tissue's mitochondria metabolic rate; however, the findings presented can bridge the gap between the changes in cellular oxidative rate and blood oxygenation.